Targeted virome deep sequencing reveals frequent herpesvirus detection in intestinal biopsies of inflammatory bowel disease patients - Jennifer-Natalia Vásquez; Pedro Doncel; Juan Camacho; Estrella Ruiz; Vanessa Recio; David Tarragó (PLoS ONE, 2025)
Background The intestinal virome is increasingly recognized for its impact on intestinal health and disease. Inflammatory bowel disease (IBD) has been linked to microbial dysbiosis, yet most studies rely on fecal samples. Here, we characterized the mucosa-associated virome directly from intestinal biopsies, providing a more localized view of viral activity at the site of pathology. Methods We conducted a retrospective metagenomic study of 56 residual intestinal biopsy samples from IBD patients including ulcerative colitis (n = 37; 66.1%), IBD-Unclassified (n = 9; 16.1%), ulcerative proctitis (n = 7; 12.5%), and Crohn’s disease (n = 3; 5.4%), applying high-throughput sequencing after viral nucleic acid enrichment using a probe-based capture approach. Metagenomic data were processed using the Chan Zuckerberg ID (CZ ID) platform. Results Viruses were detected in 58.9% (33/56) of the biopsies, primarily members of the Herpesviridae family. EBV was the most frequently detected virus (33.9%), followed by HHV-7 (21.4%), and both CMV and HHV-6 (12.5% each), after decomposing coinfections. Other viruses such as Norovirus and human papillomavirus (HPV) were detected at lower frequencies. Coinfections were also identified. No statistically significant associations were found between viral presence and IBD (ulcerative colitis, Crohn’s disease, ulcerative proctitis, and IBD-Unclassified). Conclusions Herpesviruses are rarely detected in healthy intestinal viromes and are generally considered absent, whereas their frequent presence in IBD biopsies suggests possible pathological relevance. Our findings highlight the value of metagenomic sequencing in characterizing the intestinal virome to assess the diagnostic or prognostic value of viral biomarkers in IBD.